The Quality Of Rendang Boleces Rejected Chicken With Binder Ingredients Tapioca And Mocaf Flour - Oktania, Sherly; Holinesti, Rahmi (Universitas Negeri Padang, 2022)
This research is motivated by the lack of utilization of rejected chickens, especially in West Sumatra. Dismissed chickens are laying hens that are no longer productive for laying eggs, the meat of rejected chickens has a relatively hard and tough meat texture due to the old age of the chickens, which is around 72 to 80 weeks. The purpose of this study was to analyze the quality of rejected chicken rendang boleces with tapioca flour and mocaf flour as a binder in terms of shape, color, aroma, texture and taste. This type of research is a pure experiment, with the aim of knowing the effect as well as the difference between two different variables. The research design used was a completely randomized design (CRD) with 3 repetitions. The type of data used is primary data obtained directly from 5 expert panelists by filling out the organoleptic test format. For hypothesis testing, this study uses t-test statistics, with a significant level of 5% (=0.05). The results showed that there was a significant effect on the taste quality of rejected chicken boleces, while the quality of shape, color, aroma and texture did not show any significant difference in the use of tapioca flour and mocaf flour as a binder. From this statement, it can be concluded that the indicators of the quality of the shape, color, aroma and texture of Ho are accepted because t count, < t table. While the taste quality Ho is rejected because t count > t table. The best research results are found in the use of mocaf flour on quality of shape, color, aroma, and texture, while for the taste quality the best research are produced by tapioca flour.